Perancangan Video Testimoni Pemasangan Compact Mobile Base Station Di Rumah Sakit Khusus Infeksi Covid-19 Pulau Galang Kota Batam Untuk Perusahaan PT Telekomunikasi Seluler Branch Batam - Muhammad Zaki; Jimmy Pratama (Journal of Information System and Technology (JOINT), 2020)
In the current development era, the use of print media is less effective as a promotional medium because it requires a large budget. With the presence of this video testimonial facility, customers can better understand the products they want to offer. With Video Testimonials, PT Telekomunikasi Seluler Branch Batam aims to increase the value of customer trust regarding a trademark so that customers do not turn to use other similar trademarks by presenting interviews about network quality in the area of the Special Hospital for Covid-19 Infection on Galang Island and the installation process Compact Mobile Base Station. Because there are internet network problems that cause difficulties for the community and workers in communicating in the area of the Special Hospital for Covid-19 Infection, PT Telekomunikasi Seluler Branch Batam took the initiative to install a Compact Mobile Base Station.